Patient safety in primary care: incident reporting and significant event reviews in British general practice. (25th March 2015) - Rea, David; Griffiths, Sarah
Abstract: Over the past 20 years, healthcare has adapted to the 'quality revolution' by moving away from direct provision and hierarchical control mechanisms. In their place, new structures based on contractual relationships are being developed coupled with attempts to create an organisational culture that shares learning and that scrutinises existing practice so that it can be improved. The issue here is that contractual arrangements require surveillance, monitoring, regulation and governance systems that can be perceived as antipathetic to the examination of practice and subsequent learning. Historically, reporting levels from general practice have remained low; little information is shared and consequently lessons are not shared across the general practice community. Given large‐scale under‐engagement of general practitioners (GPs) in incident reporting systems, significant event analysis is advocated to encourage sharing of information about incidents to inform the patient safety agenda at a local and national level. Previous research has concentrated on the secondary care environment and little is known about the situation in primary care, where the majority of patient contacts with healthcare occur. To explore attitudes to incident reporting, the study adopted a qualitative approach to GPs working in a mixture of urban and rural practices reporting to a Welsh Local Health Board. The study found that GPs used significant event analysis methodology to report incidents within their practice, but acknowledged under‐reporting. They were less enthusiastic about reporting externally. A number of barriers exist to reporting, including insufficient time to report, lack of feedback, fear of blame, and damage to reputations and patient confidence in a competitive environment. If incident reporting processes are perceived as supportive and formative, and where protected time is allocated to discuss incidents, then GPs are willing to participate. They also need to know how the information is used, and whether lessons are being learnt from errors.